A Comprehensive Review of Reverse Logistics in the Automotive Industry - Xumei Zhang; Jiaxuan Yu; Wei Yan; Yan Wang; Nachiappan Subramanian (IEEE Access, 2023)
Reverse logistics (RL) of automobiles has received wide attention in recent years with the innovation of resource utilization and the increase of environmental awareness. Many research papers have been published in the RL discipline focusing on the automotive industry. However, no review article is available on product-specific issues. To bridge this gap, 91 papers published in the Web of Science (WOS) database between January 2013 and March 2023 were selected and analyzed using content analysis to classify the articles into survey, evaluation, decision making, framework, modeling and review. The main findings of this paper are as follows: (1) Research on RL activities has mainly focused on recycling and remanufacturing, and insufficient research has been conducted on activities such as dismantling and waste management. (2) In terms of research objects, End-of-Life Vehicles (ELVs) and automotive batteries have received a lot of attention, while less research has been done on automotive tires, engines, waste oil, etc., which need further attention. (3) Integrated economic, environmental and social considerations are research opportunities for future evaluation and decision making. (4) The establishment of multi-objective problems and the innovation of solution methods may be the future research direction. (5) Green and sustainability themes are the main trends in the development of RL in the automotive industry in the future.